Các yếu tố ảnh hưởng đến quyết định chọn ngành nghề của sinh viên ngành Thương mại điện tử, Trường Đại học Công nghệ thông tin - Đại học Quốc gia Thành phố Hồ Chí Minh - Nguyễn Thị Hạnh, Nguyễn Thị Hạnh; Liêu Nguyễn Ngọc Quế, Liêu Nguyễn Ngọc Quế (Tạp chí Giáo dục, 2026)
The decision to choose a field of study is influenced by multiple interrelated factors, including individual characteristics, family and social contexts, and the educational environment, which makes the decision-making process complex for many students. This study aims to identify the factors affecting the choice of major among students of the E-commerce program at the University of Information Technology, Vietnam National University Ho Chi Minh City, based on a survey of 222 students. The findings indicate that individual characteristics (abilities, interests, and passion) and universityrelated factors (institutional reputation, training programs, and facilities) exert the strongest influence on students’ major choice, whereas career values and information sources have a weaker impact. Based on these results, the study suggests that career guidance should prioritize supporting students in selfassessment of personal suitability, while universities should clearly communicate their program strengths and learning environments to facilitate informed decision-making.